EVALUATION OF "BELAJAR BAHASA MANDARIN PINTAR DAN CERDAS DENGAN PANDUAN 3 BAHASA UNTUK KELAS 1 SD" - Pradono, Sudono Noto (WAHANA, 2018)
Evaluation of "Belajar Bahasa Mandarin Pintar dan Cerdas dengan Panduan 3 Bahasa untuk Kelas 1 SD" which is used for grade one elementary students is intended to know whether the textbook can be adopted or adapted by identifying the strengths and weaknesses. The result of the evaluation is that the textbook of "Belajar Bahasa Mandarin Pintar dan Cerdas dengan Panduan 3 Bahasa untuk Kelas 1 SD" cannot be adopted to be used for grade one elementary students, but itcan be adapted.